G-quadruplexes in helminth parasites - Cantara, Alessio; Luo, Yu; Dobrovolná, Michaela; Bohalova, Natalia; Fojta, Miroslav; Verga, Daniela; Guittat, Lionel; Cucchiarini, Anne; Savrimoutou, Solène; Häberli, Cécile; Guillon, Jean; Keiser, Jennifer; et al. (Nucleic acids research, 2022)
Parasitic helminths infecting humans are highly prevalent infecting ∼2 billion people worldwide, causing inflammatory responses, malnutrition and anemia that are the primary cause of morbidity. In addition, helminth infections of cattle have a significant economic impact on livestock production, milk yield and fertility. The etiological agents of helminth infections are mainly Nematodes (roundworms) and Platyhelminths (flatworms). G-quadruplexes (G4) are unusual nucleic acid structures formed by G-rich sequences that can be recognized by specific G4 ligands. Here we used the G4Hunter Web Tool to identify and compare potential G4 sequences (PQS) in the nuclear and mitochondrial genomes of various helminths to identify G4 ligand targets. PQS are nonrandomly distributed in these genomes and often located in the proximity of genes. Unexpectedly, a Nematode, Ascaris lumbricoides, was found to be highly enriched in stable PQS. This species can tolerate high-stability G4 structures, which are not counter selected at all, in stark contrast to most other species. We experimentally confirmed G4 formation for sequences found in four different parasitic helminths. Small molecules able to selectively recognize G4 were found to bind to Schistosoma mansoni G4 motifs. Two of these ligands demonstrated potent activity both against larval and adult stages of this parasite.
Keywords: Ligands; Humans; ligandy; Nematoda; genom; Platyhelminths; Genome; lidé; Parasites; zvířata; ploštěnci; cizopasní červi; hlístice; Cattle; Helminths; G-Quadruplexes; skot; G-kvadruplexy; Animals; paraziti